Scrub typhus: An emerging threat - Sayantani Chakraborty; Nilendu Sarma (Wolters Kluwer Medknow Publications, 2017)
Scrub typhus is caused by Orientia tsutsugamushi (formerly Rickettsia) and is transmitted to humans by an arthropod vector of the Trombiculidae family (Leptotrombidium deliense and L. akamushi). It is the most common re-emerging Rickettsial infection in India and many other South East Asian countries. In fact, scrub typhus is confined geographically to the Asia Pacific region, a billion people are at risk and nearly a million cases are reported every year. Scrub typhus appears particularly to be distributed in the tsutsugamushi triangle which is distributed over a very wide area of 13 million km2 bound by Japan in the east, through China, the Philippines, tropical Australia in the south, and west through India, Pakistan, possibly to Tibet to Afghanistan, and southern parts of the USSR in the north. Eschar is the characteristic lesion that starts as a vesicular lesion at the site of mite feeding. Later, an ulcer forms with black necrotic center and an erythematous border along with regional lymphadenopathy. Other features are fever, maculopapular rash starting from the trunk, and spreading to the limbs. It may affect the central nervous system, cardiovascular system, renal, respiratory, and gastrointestinal systems. Serious complication in the form of myocarditis, pneumonia, meningoencephalitis, acute renal failure, gastrointestinal bleeding, and even acute respiratory distress syndrome may develop. Tetracycline or chloramphenicol remains the main stay of therapy.